Fundamental frequency in transexual men in different stages of homonal treatment - Marsano-Cornejo, María José; Roco-Videla, Ángel; Bascuñan-Reinoso, Kimberly; Garrido-Morales, Valery; Gonzalez-Reyes, Maite; Gonzalez-Yañez, Karina; Opazo-Almazabal, Belén; Silva-Silva, Camila (Revista de Investigación en Logopedia, 2022)
The hormonal treatment that transsexual men receive has among its effects the masculinization of the voice. The objective of this research is to measure the median fundamental frequency in speech (Mf0) in transsexual men at different stages of their hormonal treatment and to determine if there is a high correlation between this parameter and the number of doses received. Using Praat, the Mf0 value of an automatic series of words, its minimum, maximum and range values ​​was obtained. Group 1: subjects with 11 or less doses of testosterone. Group 2: subjects with 12 or more doses. The values ​​found are comparable with those expected for non-transgender men. No significant differences were found with respect to Mf0, Mf0min, Mf0max and range, when comparing groups 1 and 2. There is a low correlation between the number of doses and Mf0. There is an association between hormonal treatment and masculinization of the voice, however, there is no evidence to indicate that the greater the number of doses of hormones there is a greater masculinization of the voice. New research with a larger population is needed to verify these results.